Stromal Cell-Derived Factor 1α-Stimulated Mesenchymal Stem Cells Confer Enhanced Protection Against Light-Induced Retinal Degeneration in Rats. (January 2014) - Xu, Wei; Wang, Xiao-Ting; Xu, Guo-Xing; Guo, Jian; Huang, Li-Bin
Abstract Purpose: Mesenchymal stem cells (MSCs) are currently considered to be modulators of repair in various tissues. After MSC transplant, photoreceptor rescue has been demonstrated in models of retinal degeneration. Herein, we evaluate the roles of MSCs in modulating the host reaction and photoreceptor preservation in rats suffering from light-induced retinal degeneration. Methods: Unstimulated and stromal cell-derived factor 1α (SDF-1α)-stimulated MSCs were intravenously transplanted into light-injured rats. Their photoreceptor rescue effect was compared with untreated light-injured rats and light-injured rats received only medium injection. Ciliary neurotrophic factor (CNTF) and glial fibrillary acidic protein (GFAP) expression was identified to assess host reaction post-transplantation. Retinal localization and integration of MSCs were determined by green fluorescence protein labeling. Results: MSCs were able to migrate and integrate into the host retina, and significantly inhibited retinal cell death. CNTF and GFAP were induced upregluation after MSC injection. SDF-1α stimulation elicited superior effects in both MSC migration and the inhibition of apoptosis. CNTF and GFAP expression in host retinas that received stimulated MSCs were stronger than in retinas that received unstimulated MSCs. Conclusions: Systemic administration of MSCs exerts a protective effect against light-induced retinal degeneration, and upregulates neurotrophin expression in the host retina. MSCs can be stimulated to enhance the therapeutic effect.